An integrated rural energy strategy for the Upper Tugela Location, KwaZulu - McClintock, Susan E (University of Cape Town, 2015)
Includes bibliography. === A proposal to develop the Upper Tugela Location in KwaZulu, Natal, prompted this study. This study aims to investigate the means to enhance the availability of, and access to, affordable energy sources in the Upper Tugela Location. A further aim is to match appropriate energy sources with the socio-economic conditions prevailing there. The Upper Tugela Location is an ecologically sensitive area of the Upper Tugela catchment. Rural energy planning has been criticized for the development of energy-conversion technologies while there is insufficient understanding of energy procurement practices in rural subsistence economies in South Africa. Qualitative information gained from a questionnaire survey, informal group discussions and direct observations suggest that the inhabitants of the Upper Tugela Location are relatively poor. For this reason a basic rural energy needs approach, which attempts to address the needs of the poorest, has been adopted to provide a theoretical base for the study. Research has revealed the following. Wood is the dominant energy source in the Upper Tugela Location. It is estimated that the annual household consumption of fuelwood is 3000 kg which is below the average fuelwood consumption for a rural area in South Africa. This reflects that this resource is being depleted to the degree that the local inhabitants are supplementing their use of fuelwood with expensive commercial fuels such as coal and paraffin. Locally available wood is in short supply, particularly in densely populated areas of the Upper Tugela Location. Most people are buying fuelwood from Natal farmers living on the borders of the study area. This results in an economic leakage from the Upper Tugela Location and dependence on extralocally available sources of energy. There appear to be few attempts to establish woodlots at present in the Upper Tugela Location. Equitable access to local supplies of wood are curtailed. Renewable sources of energy such as thermal and photovoltaic solar energy, micro-hydro and wind generated power, and afforestation have been investigated as have non-renewable sources of energy such as grid electricity and commercial fuels. It is concluded that no single technical option adequately addresses the energy needs of the inhabitants of the Upper Tugela Location. Most of the renewable sources of energy, except wood, are too expensive for subsistence economies and can be unreliable as they are still at the developmental stage. It is recommended that electricity from the national grid should be made available to those who can afford it. The means to improving the distribution of commercial fuels in the Upper Tugela Location should be addressed. Woody biomass management and agroforestry programmes provide the best options for an energy strategy for the Upper Tugela Location as they are inexpensive, require little maintenance, are sustainable and reliable, and serve conservation requirements at the same time.